PERAN DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU DALAM MENINGKATKAN PELAYANAN PUBLIK MELALUI APLIKASI ONLINE PERIZINAN TRANSPARAN INFORMATIF SISTEMATIS (OPTIMIS) DAN ONLINE SINGLE SUBMISSION (OSS) DI KABUPATEN BOGOR TAHUN 2020-2022 - Fatmawati, Siti Sarah; Deliarnoor, Nandang Alamsah; Sagita, Novie Indrawati (Universitas Jenderal Ahmad Yani, 2024)
The phenomenon of the Role of the One-Stop Integrated Service Investment Office in Improving Public Services through the Online Application for Transparent Informative Systematic Licensing (OPTIMIS) and Online Single Submission (OSS) in Bogor Regency is not as expected which is considered not optimal. The purpose of the research is to know and analyze the role of the One-Stop Open Service Investment Office in improving the quality of public services and to find out the factors that become obstacles. The theory used in the study, namely: Role Theory from Biddle and Thomas in Sarwono (2015: 216-217), namely: Expectation, Norm, Performance, Evaluation & Sanction. This research uses qualitative methods with interview techniques on key informants: Head of Operational Licensing Services, Head of Complaints and Services, Head of Data and Control, Head of Information, Consultation and Complaints Section, Head of Information System Development Section, Service Staff, and Service Recipients totaling 9 informants. The sampling technique used purposive sampling. Research results: The role of the One-Stop Integrated Service Investment Office has made efforts to improve Public Services through the Online Application for Transparent Informative Systematic Licensing (OPTIMIS) and Online Single Submission (OSS) in Bogor Regency. However, there are inhibiting factors for building comfort, the application system still crashes, login errors, networks, and requirements on the system that cannot upload application files, the settlement process exceeds the SOP, complaints of SK printing errors, complaints of printing errors, and lack of responsiveness to complaints.